PENGARUH MOTIVASI, KOMUNIKASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA ANGGOTA KOMPI 2 BATALYON C PELOPOR SAT BRIMOB POLDA NTB - Sudirman Sudirman; Meutia Meutia; Ketut Budiastra (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Empowerment and management of Human Resources through an organization or a conducive work environment, good communication, attitudes and behavior of superiors/leaders that will lead to job satisfaction for its members so that it can foster a loyal attitude towards the organization and in the end will have an impact on the quality of service provided. The aims of this study were to analyze and the influence of motivation, communication and leadership style on the performance of members of Company 2 Battalion C pioneer Sat Brimob Polda NTB. This type of research is included in the scope of quantitative research, because the research was conducted using research instruments in the form of questionnaires and the research aims to test the established hypotheses. The population of this study is the population in this study are members of Company 2 Battalion C pioneer Sat Brimob Polda NTB. The sample in this study using the saturated sampling method was chosen because the number of population in Company 2 Battalion C pioneer of Brimob Polda NTB is relatively small. So the number of samples in this study were 95 respondents. After analyzing the validity and reliability of the instrument, the data was analyzed using multiple linear regression. The results of the study concluded that motivation had an effect on the performance of Brimob members. Another variable, namely organizational communication, has a positive effect on the performance of Brimob Battalion C members of the NTB Police. Leadership style has no effect on the performance of members of the Mobile Brigade Battalion C Polda NTB. Based on the value of the Standardized Coefficients Beta, it can be seen that the motivation variable is the most dominant variable that affects the performance of members of the Mobile Brigade Battalion C Polda NTB.